(untitled) (Journal of Hama University, 2024)
It is considered sectarian fanaticism one of the contradictory thing with spirit of sharia law and the principles of Islam, but it is considered one of the rejected things that are not accepted by reason and logic there are also many frantic attempts to undermine the lofty edifice of this religion through these loopholes, which called for such research, to be a contribution to revealing the truth of this tendency in ancient jurisprudential interpretation works, and explaining its ergative impact on impact on this great heritage As well as explaining the most important factors and reasons that led to this. Then explaining the importance of freedom from it and preserving our Islamic heritage pure from and impurity.One of the most important goals of this research is constructive criticism that contributes to bringing viewpoints closer together, drawing the attention of researchers in this field to be careful not to make the same mistakes, which the applicants signed in order for this research to achieve its desired goal, I have divided it into four demands, first of them was devoted to a number of examples 0f sectarian fanaticism in interpreting verses of jurisprudential rulings, the second is for its most important reasons, the third is for its most important effects, and the fourth is for the importance of freedom from this type of sectarian fanaticism one of the most important results reached by the research is that the interpreter is not judged to be fanatical without the evidence that confirms that, and the fanaticism that explains his doctrine does not necessarily mean that who disagree with his opinion are incorrect, interpretive opinions must be taken from approved sources, and freedom from sectarian fanaticism preserves our heritage with high credibility without closing the door to positive, constructive criticism .